MRSA and VRE Colonization in Solid Organ Transplantation: A Meta‐Analysis of Published Studies. Issue 8 (8th July 2014) - Ziakas, P. D.; Pliakos, E. E.; Zervou, F. N.; Knoll, B. M.; Rice, L. B.; Mylonakis, E.
<x xml:space="preserve">Abstract</x> The burden of methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant enterococcus (VRE) colonization among the increasing number of solid organ transplant patients has not been systematically explored. We searched PubMed and EMBASE for pertinent articles, performed a meta‐analysis of prevalence across eligible studies and estimated the risk of ensuing MRSA or VRE infections relative to colonization status. We stratified effects in the pretransplant and posttransplant period. Twenty‐three studies were considered eligible. Seventeen out of 23 (74%) referred to liver transplants. Before transplantation, the pooled prevalence estimate for MRSA and VRE was 8.5% (95% confidence interval [CI] 3.2–15.8) and 11.9% (95% CI 6.8–18.2), respectively. MRSA estimate was influenced by small studies and was lower (4.0%; 95% CI 0.4–10.2) across large studies (>200 patients). After transplantation, the prevalence estimates were 9.4% (95% CI 3.0–18.5) for MRSA and 16.2% (95% CI 10.7–22.6) for VRE. Pretransplant as well as posttransplant MRSA colonization significantly increased the risk for MRSA infections (pooled risk ratio [RR] 5.51; 95% CI 2.36–12.90 and RR 10.56; 95% CI 5.58–19.95, respectively). Pretransplant and posttransplant VRE colonization were also associated with significant risk of VRE infection (RR 6.65; 95% CI 2.54–17.41 and RR 7.93; 95% CI 2.36–26.67, respectively). Solid organ transplantation is a high‐risk setting for MRSA and VRE colonization, and carrier state is associated with infection. Upgraded focus in prevention and eradication strategies is warranted.